Cryptic Antimicrobial Peptides: Identification Methods and Current Knowledge of their Immunomodulatory Properties - Pizzo, Elio; Cafaro, Valeria; Di Donato, Alberto; Notomista, Eugenio (Current Pharmaceutical Design, 2018)
Cationic antimicrobial peptides (CAMPs), also known as host defence peptides (HDPs), are essential evolutionarily conserved components of innate immunity, constitutively or inducibly expressed in response to invasion by pathogens. In addition to a direct antimicrobial action, they are able to synergistically operate with other defence molecules to combat infection by neutralization of endotoxins, chemokine-like activities, induction of angiogenesis and wound repair. The importance of CAMPs has been highlighted in animal models and supported by observations in patient studies. CAMPs are attractive alternative candidates to antibiotic treatment, because they offer several advantages over the currently used drugs, moreover, knowledge on these peptides, especially regarding the intertwinement between their structure, function and mechanism of action, could be applied in the rational design of antimicrobial/anti-inflammatory/wound healing enhancing drugs. CAMPs combat pathogens by targeting bacterial membranes and essential membrane-related functions, and, in some cases, also target intracellular components. Despite differences in their size and sequence, many of them share a net positive charge and fold into amphipathic structures after contact with bacterial surfaces or endotoxins like lipopolysaccharides and lipoteichoic acid. Due to their peculiar mechanism, acquisition of resistance towards these peptides would be difficult for the bacteria. Very interestingly it has been demonstrated that several proteins, including proteins apparently not involved in immunity, can behave as sources of CAMPs hidden in their primary structures and released by the action of host and/or bacterial proteases. The existence of these “cryptic CAMPs” suggests that the panel of antimicrobial peptides present in higher eukaryotes and the variety of functions they perform could be much wider and more complex than previously suspected. This review focuses on source, structure and mechanism of action of cryptic CAMPs, with special attention to their immunomodulatory functions.
Keywords: immunomodulation